Defining components and measuring the effects of audiologist-delivered counselling for tinnitus - Thompson, Dean Mark (2018)
Psychological treatment is effective at alleviating tinnitus distress when delivered by a psychologist. In the United Kingdom (UK), best practice guidance for tinnitus advises that audiologists should deliver Cognitive Behavioural Therapy (CBT) and other counselling techniques where psychologists are unavailable. However, there is a lack of evidence for the effectiveness of audiologist-delivered psychological tinnitus treatment, and no consensus among clinicians and researchers on what form, if any, this should take. Furthermore, training in CBT and other counselling techniques is not a part of standard audiologist training in the UK. The aims of this PhD were to define the components and measure the effects of an audiologist-delivered psychological tinnitus treatment for people with tinnitus.